آیتِ کریمہ يَاأَيُّهَا الَّذِينَ آمَنُوا لَا تَقُولُوا رَاعِنَا وَقُولُوا انْظُرْنَا سےحجیتِ سدُالذرائع پر ابنِ حزم کےمعارضہ کا تجزیاتی مطالعہ: An Analytical Study of the Ibn-e-Hazam’s Objections to Authenticity of the Sadd-o-Zaree'ah - Fakharuddin, Muhammad (Al-Amīr Research Journal for Islamic Studies, 2021)
As well as per Shariah, it is admissible and some of the time even mandatory to save the devotees from the activities that might lead them towards the prohibited exercises. Consequently, the decision of denial from these kinds of exercises is called Sadd-e-Zaree'a. This is the guideline derived from the Quran and Sunnah. As Almighty Allah prohibited the devotees to say 'Raina' because this word was utilized by Jews purposely in an off-base way with underhanded aims, while, Muslims introduced their solicitations by this equivalent word in the most elevated court of The Holy Prophet (harmony and gifts arrive) for looking for effortlessness and unwinding in their concerned issues. As in Quran: O People who Believe, don't tell (the Prophet Mohammed-harmony and gifts arrive), "Raina (Be accommodating towards us)" however say, "Unzurna (Look leniently upon us)", and listen mindfully in any case. [Baqarah 2:104]. (To disregard the Holy Prophet - harmony and endowments arrive - is impiety.) Ibn Hazm in his famous book Al-Aḥkām Fī ūṣūl Al-Aḥkām has objected to the mentioned verse from which jurists have taken the argument of Sadd-e-Zaree'a. Because the Zahiri school of thought is based on the appearance of the text (Quran o Hadees). This is why Ibn Hazm Zahiri denies it (the source of Shariah), and proves that accepting the source of Shariah is an increase in religion which is in itself illegitimate as well as the opposition of the Prophet (peace and blessings of Allah be upon him). There is also the addition of items by their thoughts in Shariah. In the above article, an analytical study of the objections of Allama Ibn Hazm will be presented, explaining the sources and the arguments as to whether or not their source is Shariah.